Analisis Tingkat Kepuasan Konsumen Terhadap Kualitas Pelayanan Roti Unyil Bakery - Supriyanti, Yanti; Nurselvi (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2024)
PT. XYZ is a bakery industrial company founded in 1992 with employees consisting of only 5 people with new types of bread consisting of 5 types, namely round bread with cheese filling, round bread with chocolate filling, bread with chocolate banana filling, bread with cheese banana filling, and bread with meat filling. The bread that is made is smaller than bread in general, so it is better known as unyil bread. In 2018 PT. XYZ managed to sell around 2,167,250 pcs, in 2019 total sales decreased by 107,225 or around 5.21%. In 2020 the decline was quite significant, namely 481,332 pcs or 30.48%. In 2021 there will still be a decline of 327,945 or 26.22%. One of the factors thought to have caused the decline in sales at PT. XYZ is consumer dissatisfaction. This research aims to evaluate the level of customer satisfaction with service quality at Roti Unyil Bakery (PT. The research results show that the Assurance and Reliability dimensions have the highest satisfaction scores, while the Responsiveness and Empathy dimensions require improvement to increase customer satisfaction. Based on IPA analysis, several service attributes are in the improvement priority quadrant, indicating the need to improve aspects of customer service. This research provides strategic recommendations for PT. XYZ improves service quality to retain consumers.